Historians and Their Duties - Gorman, Jonathan (History and theory, 2004)
We need to specify what ethical responsibility historians, as historians, owe, and to whom. We should distinguish between natural duties and (non-natural) obligations, and recognize that historians' ethical responsibility is of the latter kind. We can discover this responsibility by using the concept of “accountability”. Historical knowledge is central. Historians' central ethical responsibility is that they ought to tell the objective truth. This is not a duty shared with everybody, for the right to truth varies with the audience. Being a historian is essentially a matter of searching for historical knowledge as part of an obligation voluntarily undertaken to give truth to those who have a right to it. On a democratic understanding, people need and are entitled to an objective understanding of the historical processes in which they live. Factual knowledge and judgments of value are both required, whatever philosophical view we might have of the possibility of a principled distinction between them. Historians owe historical truth not only to the living but to the dead. Historians should judge when that is called for, but they should not distort historical facts. The rejection of postmodernism's moralism does not free historians from moral duties. Historians and moral philosophers alike are able to make dispassionate moral judgments, but those who feel untrained should be educated in moral understanding. We must ensure the moral and social responsibility of historical knowledge. As philosophers of history, we need a rational reconstruction of moral judgments in history to help with this.